Outcome of ivermectin treated mild to moderate COVID-19 cases: a single-centre, open-label, randomised controlled study (IMC Journal of Medical Science, 2021)
Background and objectives: Various existing non-antiviral drugs are being used to treat severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection based mostly on existing data from previous coronavirus outbreaks. Ivermectin is one of such agents being widely used to treat early-stage of COVID-19. This study evaluated the outcome of ivermectin treated mild to moderate COVID-19 cases compared to usual care.Methods: This open-label randomised controlled study was conducted at a sub-district (Upazila) health complex from 1st May 2020 to the end of July 2020. Consecutive RT-PCR positive eligible COVID-19 patients were randomised into control and intervention arms. In the intervention arm, ivermectin 200 micrograms/kg single dose was administered orally in addition to usual care and was followed up till recovery. Repeat RT-PCR was done on day ten since the first positive result. The end point with regard to treatment outcome was time required for the resolution of symptoms from the onset of the symptoms and following enrollement in the study.Results: A total of 62 mild to moderate COVID-19 patients were enrolled in the study. There were 30 patients in the control arm and 32 patients in the intervention arm. Total recovery time from the onset of symptoms to complete resolution of symptoms of the patients in the intervention arm was 10.09 ± 3.236 days, compared to 11.50 ± 5.32 days in the control arm (95% CI -0.860,3.627, p>. 05) and was not significantly different. The mean recovery time after enrolment in the intervention arm was 5.31 ± 2.48 days, which also did not differ significantly from the control arm of 6.33 ± 4.23 days (95% CI – 0.766, 2.808, p> 0.05). Results of negative repeat RT- PCR were not significantly different between control and intervention arms (control 90% vs intervention 95%, p>.05).Conclusion: Ivermectin had no beneficial effect on the disease course over usual care in mild to moderate COVID-19 cases.Ibrahim Med. Coll. J. 2020; 14(2): 11-18